2020
DOI: 10.9734/jabb/2020/v23i130133
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemistry and Biological Activities of Leaves and Pulp Extracts from Ziziphus mauritiana (Lam.) Collected in Mali

Abstract: Introduction: The objectives of this work consisted of a phytochemical study of the leaves and pulp of Ziziphus mauritiana Lam collected from the flooded and dried sites of Niono and Sévaré in Mali and to evaluate the biological activities of the extracts, i.e. the antiradical activity and hemolytic activity. Methods: Phytochemical analysis and biological activities were performed at the plant biochemistry and biotechnology laboratory of the FST / USTTB. The tannins and flavonoids were extracted by macer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…The results obtained from the present work are in agreement with the data from others studies which show that local plants could improve the regulation of the molecular mechanisms involved in diabetes control due to their bioactive compounds [ 14 , 21 ]. Polyphenols and flavonoids are especially evident in antioxidant, anti-inflammatory, antimicrobial, antihypertension, and antidiabetic processes in the human body [ 22 , 23 , 24 ]. These findings support the results of our recent survey, which showed that the local population in Mali uses the fruits of these two species for the traditional treatment of hypertension [ 5 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The results obtained from the present work are in agreement with the data from others studies which show that local plants could improve the regulation of the molecular mechanisms involved in diabetes control due to their bioactive compounds [ 14 , 21 ]. Polyphenols and flavonoids are especially evident in antioxidant, anti-inflammatory, antimicrobial, antihypertension, and antidiabetic processes in the human body [ 22 , 23 , 24 ]. These findings support the results of our recent survey, which showed that the local population in Mali uses the fruits of these two species for the traditional treatment of hypertension [ 5 ].…”
Section: Resultsmentioning
confidence: 99%
“…Flavonoids were determined using the aluminum trichloride reagent (AlCl 3 ) according to the protocol described by Keita et al [ 23 ]. This involved the addition of 500 μL of extract to 2 mL of distilled water and 150 μL of 5% sodium nitrite (NaNO 2 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In other side, to face up the resurgence of antimicrobial-resistant pathogens, the researchers worldwide are hardworking to find other alternative sources of drugs and bioactive chemical compounds of plant origin [3] that would serve as antimicrobial agents less expensive, less toxic, and more effective [4]. This is why, many plants have been explored as alternative sources of drugs and in particular antimicrobial and anti-inflammatory agents [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%